Multiple extra macular branch retinal vein occlusions in hyperhomocysteinemia - Gore, Abhijit Diwakar (Medknow Publications & Media Pvt Ltd, 2014)
Hyperhomocysteinemia is a well-known modifiable risk factor for thromboembolism. Retinal vascular occlusion in patients having hyperhomocysteinemia is a known entity, particularly in young patients. However, multiple extra macular branch retinal vein occlusion (BRVO) is a rare condition, which can be a presentation of this disease. We present a patient who had multiple extra macular BRVO; on complete systemic workup, he was found to have raised homocysteine levels.